Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1089/rej.2008.0668
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Endothelial Cells Derived from the Murine Embryonic Stem Cell Line CCE

Abstract: Embryonic stem cells (ESC) are defined by two main properties of self-renewal and their multipotency to differentiate into virtually all cell types of the body, including endothelial cells. ESCs have been widely regarded as an unlimited source of cells in regeneration medicine and also an ideal in vitro model to investigate complex developmental processes. Here, we report a simple and efficient in vitro model to derive a nearly pure population of endothelial cells from a murine ESC line. CCE ES cells are expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that VEGF treatment of murine ES cells grown on type IV collagen (a component of Matrigel) coated plates [3] or on Matrigel [27] undergo vasculogenesis. In addition, EB treated with VEGF grown in the presence [28] or absence [13] of Matrigel undergo vasculogenesis.…”
Section: Formation Of Vascular Tubes In Matrigelmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that VEGF treatment of murine ES cells grown on type IV collagen (a component of Matrigel) coated plates [3] or on Matrigel [27] undergo vasculogenesis. In addition, EB treated with VEGF grown in the presence [28] or absence [13] of Matrigel undergo vasculogenesis.…”
Section: Formation Of Vascular Tubes In Matrigelmentioning
confidence: 99%
“…Although previous studies have demonstrated that VEGF treated murine or human ES cells or EB are capable of vascular sprouting [25,27,45] the mechanism of lumen formation was not explored. Since we observed apoptotic cells inside the vascular tubes, it is possible that the sprouts begin as solid tubes and form lumina by apoptotic loss of central cells.…”
Section: The Inhibition Of Eb Formation By Anti-ceacam1 Mab Cc1 Extenmentioning
confidence: 99%
See 1 more Smart Citation
“…The functionality of the cells was confirmed by their ability to form capillary network in presence of vascular endothelial growth factor (VEGF) (8). Differentiation of the ECs from different sources inducing the angioblast in the embryo (8), the endothelial progenitor cells (EPCs), mesoangioblasts and multipotent progenitor cells-(MAPCs) or side population in the adult bone marrow (2,9) and murine embryonic stem cell line (10) has been reported (11). Various surface markers such as CD34, CD146, vascular endothelial growth factor 2 (VEG FR2) which is sometimes referred as KDR, tie 2, endothelial cadherin and E-selection have been used to identify the stem cell contributing to angiogenesis (12)(13)(14).…”
Section: Introductionmentioning
confidence: 98%
“…Differentiation of the endothelial cells (ECs) from different sources including the angioblast in the embryo (Mikkola and Orkin, 2002), the EPCs, mesoangioblast and multipotent adult progenitor cells (MAPCs) or side population in the adult bone marrow (Luttun et al, 2002;Reyes et al, 2002) and a murine embryonic stem cell line (Fathi et al, 2008) has been reported. According to Rehman et al (2003), EPCs contribute to vessel growth by releasing angiogenic growth factors.…”
Section: Introductionmentioning
confidence: 99%